Non-intrusive hydro-geophysical characterization of the unsaturated zone of South India-A case study. (October 2016) - Arora, Tanvi; Boisson, Alexandre; Ahmed, Shakeel
Abstract: The unsaturated zone is the gateway for water movement from the land surface to the saturated zone. The amount of recharge to aquifer, related to the percolation, is constrained by the characteristics of the unsaturated zone. Unsaturated zone research is still needed to understand the flow paths of the recharge through it, particularly in heterogeneous media. One possibility for this understanding is to use time lapse electrical resistivity tomography [TLERT]. However, the relationship between moisture and electrical resistivity changes still need to be investigated. A time lapse electrical resistivity tomography experiment was carried out in the unsaturated zone of granitic terrain at National Geophysical Research Institute, Hyderabad to develop a relationship between soil moisture and electrical resistivity changes. The measurements of soil moisture using neutron probe and resistivity from TLERT images were correlated. To extend the spatial information between point measurements using neutron probe, a variographic analysis was performed. Variograms were computed using MS-EXCEL to ensure a desired number of pairs for a variogram. The two different datasets (resistivity and moisture) were amalgamated on a common platform by geostatistical tools to relate the soil moisture and resistivity. A relation is established between moisture variations in the form of saturation versus the resistivity. This relation has been tested both from an experiment in laboratory and in field. It shows that initially a non-linear relation exist between soil moisture and resistivity. However, the resistivity becomes invariant even with the moisture increase in the range of 11%–13%. Recharge is reflected in resistivity images by a decrease, along the preferred permeable zones. Since the unsaturated zone exhibit extremely high variability, both in space and time, the surface geophysical investigations such as TLERT (Time Lapse Electrical Resistivity Tomography) is a useful method to characterize flow in the vadose zone, which is not possible with point measurements alone. Highlights: Time Lapse Electrical Resistivity Tomography [TLERT] for the unsaturated zone. Spatio-temporal monitoring of the soil moisture movement. Relationship between resistivity and moisture. Quantitative estimation of natural recharge.